The Relationship Between Arm Flexibility and Muscle Strength and The Results of Gyaku Tsuki Karate Punching Ability - Tri Ardilaini; Reza Resah; Destriani (Universitas Negeri Semarang, 2025)
The aim of this research was to determine the relationship between arm flexibility and arm muscle strength on the results of Gyaku Tsuki karate blows at the Sukawinatan Palembang dojo. The method used in this research is correlation using quantitative methods. The population of this study were all karate athletes at the Sukawinatan Palembang dojo with a total sample of 30 people. The data analysis technique used is correlation and regression techniques with a significance level of 70.5% or 0.05. The results of the study showed that there was a significant relationship between Gyaku Tsuki’s arm muscle strength in the martial art of karate, while arm flexibility and Gyaku Tsuki’s punch results had no partial relationship. Simultaneously, the research results show that there is a certain relationship between arm flexibility and arm muscle strength and the results of Gyaku tsuki karate blows at the Palembang Sukawinatan dojo. The conclusion of this research is that there is a relationship between arm flexibility and arm muscle strength and the results of Gyaku tsuki Karate blows at the Sukawinatan Palembang dojo.